Obtenção de carreadores lipídicos nanoestruturados contendo clobetasol e tacrolimus e avaliação da permeação cutânea - Andrade, Lígia Marquez (2014)
The use of topical medications, such as clobetasol propionate (CLO) and tacrolimus (TAC) is the main treatment for inflammatory skin diseases including discoid lupus erythematosus (DLE). The DLE is a chronic disease that affects the skin and its treatment can be improved with the simultaneous use of these drugs. However, this condition is difficult to treat topically because of the thickening of the stratum corneum (SC). New formulations such as lipid nanoparticles and the use of permeation enhancers can improve drug penetration in the skin and improve the topical treatment of different pathologies. Therefore, the aim of this study was to develop and characterize nanostructured lipid carriers (NLC) containing TAC and CLO and NLC coated or not with chitosan oligosaccharide (CO), in order to increase the skin permeation and retention of drugs. NLCs were prepared by the dilution of the microemulsion and were subsequently coated with OQ. The carriers obtained contained both drugs or TAC or CLO separately. The formulations obtained were evaluated for average diameter and polydispersity index (PDI), zeta potential, drug recovery (DR), encapsulation efficiency (EE) and drug loading (DL). The drug penetration from the NLC was assessed in pig ear skin in Franz cells. Co-encapsulated NLCs showed an average diameter of 143.3 nm and PdI of 0.264. The particles showed negative zeta potential of about -40 mV. After coating with OQ, NLCs showed a significant increase in diameter (311.9 nm) (p <0.05) and positive zeta potential (24,4mV) due to the adsorption of CO on the surface of the NLC. Co-encapsulation of the drug was effective, EE was greater than 90% for both TAC and CLO. In studies of electron paramagnetic resonance (EPR) it was observed that the drugs slightly modified the dynamics of lipids in NLC on the surface of the matrix (5-DSA). There was a significant increase in the 2A// parameter, the TAC+CLO-NLC (47,1G) compared to NLCs with no drug (45,6G). When the samples were coated with CO, the lipid dynamic modified considerably. The 2A// values increased from 45.5 to 50.1 in the NLC and 46.5 to 50.7 in the TAC+CLO-NLC. The CO probably forms a frame around the nanocarriers which significantly reduces the lipids mobility. The encapsulation of the drugs increased penetration of both TAC and CLO to the skin layers when compared to non-encapsulated drugs. The NLC coated increased the amount of TAC retained in the deeper layers of the skin (approximately 1.8 times more drug). For the CLO, the coating favored retention in the EC (1.7 fold) and on the remaining skin (3 times more drug) as compared to uncoated particles. When co-encapsulated with TAC and CLO, TAC’s penetration was superior compared with the particle containing only TAC. Thus, this strategy has shown to be promising to increase TAC’s skin penetration , which is a drug that hardly passes through the SC and promote greater retention of CLO in the upper layers of the skin. The results suggest that the co-encapsulated system is a potential formulation for skin drug delivery of the drugs.